The Interest of Grade V Male Students in Traditional Sports Material in Physical Education Sports and Health at Geluran 3 Elementary School Taman Sidoarjo - sulistyo, Mochammad Bhagas; Sudijandoko, Andun (STKIP Paasundan Press, 2023)
The purpose of this study was to determine the interest of grade V male students in traditional sports materials in health education at Geluran 3 Taman Sidoarjo State Elementary School. This is very necessary for students as a form of awareness in recognizing customs and traditions in the country of Indonesia. This research design is quantitative descriptive research and how to collect data by filling out a questionnaire. The sample of this research is all fifth grade male students at Geluran 3 Taman Sidoarjo State Elementary School, totaling 61 students. The results of this study indicate that the interest of fifth grade male students in traditional sports material in PE at Geluran 3 Taman Sidoarjo State Elementary School, for the very low category as many as 6 students or 9.83%, low category as many as 6 students or 9.83%, medium category as many as 32 students or 52.46%, high category as many as 13 students or 21.31%, very high category as many as 4 students or 6.56%.